Pengembangan Media Pembelajaran Komik Digital pada Materi Wujud Zat dan Perubahannya Kelas IV Sekolah Dasar - Setiani, Ruri Novia; Kartono, Kartono; Halidjah, Siti (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This research primarily aims to develop digital comic learning media for fourth-grade elementary school students, focusing on the topic of substances and their changes. The method employed in this research is development research (R&D) using the ADDIE development model. The research involved 26 fourth-grade students from State Elementary School 05 South Pontianak and two expert validators, one specializing in media and the other in material. Data collection techniques included interviews and questionnaires. The findings indicated that the development of the digital comic learning media followed four research steps: analysis, design, development, and implementation. The product's feasibility was evaluated and achieved a